ANALISA PERAN SERIKAT PEKERJA DAN BUDAYA ORGANISASI TERHADAP KESEJAHTERAAN PEKERJA (STUDI KASUS PADA PT. TRANSPORTASI JAKARTA): (Studi Kasus Pada PT. Transportasi Jakarta) - Oratmangun, Jan; Dwianto, Agung (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This study examines the roles of labor unions and organizational culture in enhancing employee well-being at PT. Transportasi Jakarta. Employing a qualitative approach, this research analyzed in-depth interview data from labor union representatives, management, and employees. The findings reveal that labor unions play a significant role in advocating for employee welfare through collective bargaining and educational programs. An inclusive and collaborative organizational culture also contributes to increased job satisfaction and productivity. However, the study identifies several challenges, such as managerial resistance to change and tensions between traditional values and the demands of modernization. The interaction between labor unions and organizational culture creates a complex dynamic, where collaboration yields positive synergies, but conflicts can arise due to differing perspectives. Overall, this study concludes that employee well-being is shaped by the interplay of various factors, and collaborative efforts between labor unions and management are crucial for achieving sustainable well-being.Keywords: labor unions, organizational culture, employee well-being, advocacy, industrial relations, PT. Transportasi Jakarta